KHUDOYARKHAN'S LAST RETURN TO POWER IN LOCAL SOURCES - Nabijonov Sirojiddin Abdumutalib O‘g‘li (Western European Studies, 2025)
The study of relations between Uzbek khanates and neighboring states in the 1860s– 1870s remains a relevant scientific direction today. In particular, it is important to examine and analyze the political and economic processes that occurred in the Khanate prior to the establishment of the Turkestan General-Governorate in 1867, especially events between 1865– 1866. This article investigates the initial policies of Khudoyarkhan of Kokand (r. 1865–1875) and their influence on the neighboring state of the Bukhara Khanate and the Turkestan region using a comparative-analytical approach based on a number of local sources. The article also highlights significant historical developments in the internal affairs of the khanate during this period.
Keywords: Bakhodirkhantura Kosoni; diplomatic distrust; nepotism